Changes in The Available Micronutrient Status During Amelioration of Soils Irrigated with High RSC/Saline Water - Joshi, D C (Annals of Arid Zone, 2016)
Studies on the changes in available micronutrient status during amelioration of soils irrigated with high RSC/saline water have been reported. In soils irrigated with high residual sodium carbonate water, reducible Mn had significant positive influence on DTPA extractable Zn and significant negative effect on Cu. In saline - water irrigated amended soils, positive influence of reducible Mn on DTPA extractable Mn was further improved.